Elevated highly sensitive C-reactive protein and d-dimer levels are associated with food insecurity among people living with HIV in Pune, India. Issue 11 (4th March 2019) - Patil, Sandesh; Kadam, Dileep; Mehtani, Nicky; Sangle, Shashikala; Marbaniang, Ivan; Kulkarni, Vandana; Shere, Dhananjay; Deshpande, Prasad; Dhumal, Gauri; Suryavanshi, Nishi; Gupte, Nikhil; Bollinger, Robert; et al.
Abstract: Objective: To assess the prevalence and determinants of food insecurity among people living with HIV (PLWH) in Pune, India and its association with biomarkers known to confer increased risks of morbidity and mortality in this population. Design: Cross-sectional analysis assessing food insecurity using the standardized Household Food Insecurity Access Scale. Participants were dichotomized into two groups: food insecure and food secure. Logistic regression models were used to assess associations between socio-economic, demographic, clinical, biochemical factors and food insecurity. Setting: Antiretroviral therapy (ART) centre of Byramjee Jeejeebhoy Government Medical College and Sassoon General Hospitals (BJGMC–SGH), Pune, a large publicly funded tertiary and teaching hospital in western India. Particpants: Adult (≥18 years) PLWH attending the ART centre between September 2015 and May 2016 who had received ART for either ≤7d (ART-naïve) or ≥1 year (ART-experienced). Results: Food insecurity was reported by 40 % of 483 participants. Independent risk factors (adjusted OR; 95 % CI) included monthly family income <INR 5000 ( 70 USD; 13·2; CI 5·4, 32·2) and consuming ≥4 non-vegetarian meals per week (4·7; 1·9, 11·9). High-sensitivity C-reactive protein (hs-CRP) ≥0·33 mg/dl (1·6; 1·04, 2·6) andd -dimer levels 0·19–0·31 µg/ml (1·6; 1·01, 2·6) and ≥0·32 µg/ml (1·9; 1·2, 3·2) were also associated with food insecurity. Conclusions: More than a third of the study participants were food insecure. Furthermore, higher hs-CRP andd -dimer levels were associated with food insecurity. Prospective studies are required to understand the relationship between food insecurity, hs-CRP andd -dimer better.